Report of the tenth regular meeting of the inter-american board of agriculture - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura, 2021)
270 páginas; versión en inglés: 280 páginas pdf.